Estudio jurídico doctrinario al numeral 4 del artículo 640 del Código Orgánico Integral Penal-procedimiento directo, en relación al plazo de la sustanciación de la audiencia de procedimiento directo, el mismo que vulnera el debido proceso, derecho a la defensa y la presunción de inocencia - Guamàn Yumi, Lenin Anibal (2016)
In the Code of Criminal Integral they have joined "special procedures", depending on the severity of injuries criminally legal rights and created "direct" and "expeditious" trial, in order to achieve efficient criminal proceedings; As we understand, which it aims to create the prompt response of justice, to provide public safety and promote the protection of the victim, since the extension of time in the process, always generated social concern and above all impunity and helplessness . With the issuance of the Code of Criminal Integral, COIP three types of procedures for the conduct of criminal proceedings, as stated in Articles 580, 634 and 647, which are the "ordinary" recognized, "special procedures"; and the "procedure for the private exercise of criminal action." This procedure is new in our criminal procedural structure concentrates all stages in a single hearing and proceeds to qualified as gross crimes, but punished with a maximum prison sentence of up to five years; the definition of flagrante delicto, is described in Article 527 of the COIP, stating: "found in flagrante delicto, the person committing the crime in the presence of one or more persons or when discovered immediately after their alleged commission, whenever there is a continuous persecution since the time of the alleged commission until apprehension, also when you are with weapons, instruments, the product of illicit, prints or documents relating to the new offense. No hot pursuit may invoke if it has been more than twenty-four hours between the commission of the offense and apprehension. " Direct procedure also applies to property crimes, an amount not exceeding 30 unified basic wage of workers in general, classified as flagrant; but they are excluded from this procedure efficient offenses against public administration or affecting the interests of the state, crimes against the sanctity of life, integrity and personal liberty resulting death, crimes against sexual and reproductive integrity and crimes of violence against women or members of the household. The judge of criminal guarantees, belonging to the flagrancy unit is competent to substantiate and resolve the direct method, which is overcome any legal dispute regarding the competition as to learn, process and sentencing by direct procedure the competent He is the judge of criminal guarantees and not the court of criminal law, and for the sole judge is the only one who can know it and have the procedure to be followed is the direct, as expressed in Article 529 COIP when he says: "In cases flagrant infringement, within twenty-four hours after the arrest took place, the corresponding oral hearing before the judge or, where the legality of the arrest will qualify will be made. The prosecutor or, if deemed necessary, make charges and asked if applicable precautionary and protective measures that the case merits and the process will be determined "; after he has qualified the flagrancy; for which, the judge shall, within 10 days (counting from the audience of flagrante delicto), convened for the realization of direct trial hearing, which will pronounce sentence. In this research a legal and doctrinal detailed analysis of the direct process the same previously described, this study must show that it violates due process, right to defense and the presumption of innocence will be made, taking into consideration the following "Once the judge qualified flagrancy indicate the day and time to be carried out corresponding adjudication hearing, within ten days," thus the right to defense is violated, since within ten days, the litigants may not submit a proper defense technique for scarce ten days time and once this term test defunct relevant witnesses who witnessed the incident and thus the parties may be defenseless might appear, Likewise, when the parties request it tests that require the intervention of technicians, experts or doctors, within ten days those officials do not have the adequate time to deliver such expertise. This procedure from a legal point of view has become a machine to make statements condemning innocent as the term in which it is determined that the test can be performed is not enough as it was corroborated in the present investigation of this form violates the right to presumption of innocence defense and due process.